Depression : the sun always rises - Ashmore, Margaret, 1953- (Phillipsburg, NJ : P & R Pub., 2013)
Choosing God's light in a world's darkness. The periods of depression that we all share can range from having a bad day to grieving the loss of a loved one. Our fallen world harbors a broad spectrum of suffering that, while never the same for each individual, has always been part of the human condition. Yet Margaret Ashmore reminds us that however difficult our circumstances, they cannot determine whether our lives are ruled by joy or by depression; the choices we make in light of those circumstances do. She lays before us a set of godly choices we can make in our own "dark night of the soul" to seek God's freedom from our dominating depression. The Gospel for Real Life booklet series by the Association of Biblical Counselors (ABC) applies the timeless hope of Christ to the unique struggles of modern believers. - Back cover.
The normality of depression -- The power to choose -- The dark night of the soul -- Choose gratitude -- Choose to see God's sovereign love -- Choose to relinquish rights -- A good exercise -- Choose to dwell on truth -- Choose to move forward -- Choose a Christ-centered, not a self-centered life -- Conclusion. The gospel of salvation -- Additional resources.
Includes bibliographical references (pages 37-38).
Keywords: Depressed persons -- Religious life; Depression, Mental -- Religious aspects -- Christianity